Social dialogue in the public service in selected countries of the European Union - Bordogna, Lorenzo (Geneva, 2018)
"Social dialogue, including collective bargaining, is one of the core enabling principles of the ILO’s decent work agenda. It should form part and parcel of the regulation of labour relations in the public sector. Dialogue and bargaining can and should be key contributors to public sector efficiency, performance and equity. However, because competing interests can be involved, neither dialogue nor collective bargaining is conflict-free. If governments and public sector unions are to be encouraged to bring these dynamics into public sector work, where industrial peace carries a special premium in the public mind, then considerations of conflict management must be uppermost. This is more relevant than ever in times of fiscal consolidation and austerity measures. The Global Dialogue Forum on Challenges to Collective Bargaining in the Public Service, held in Geneva on 2-4 April 2014, concluded with a recommendation that the Office carry out research on the diversity of practices in social dialogue, in particular collective bargaining, in different countries. Such research should provide countries with knowledge to improve their own practices, enable improved responses to situations of crisis and to address obstacles in the ratification of Conventions Nos. 151 and 154. Building upon this foundation and in celebration of the 40th anniversary of Convention No. 151, this paper, drafted by Professor Lorenzo Bordogna of the University of Milan, presents a compilation of practices in collective agreements in the public service in the European Union. This selection shows how the principles of Convention No. 151 have been implemented through legislation and/or collective bargaining."